Jawapan

2016-02-12T11:03:58+08:00
(2x - 1) (x + 4) = k (x - 1) + 3
2x² + 8x - x - 4 = kx - k + 3
2x² + 7x - kx - 4 + k -3 = 0
2x² + (7 - k)x - 7 + k = 0

3m = -7 + k
3m + 7 = k
 
 -7 + k = 3 + m
 -7 + (3m + 7) = 3 + m
3m = 3 + m
2m = 3
 m = 3/2
 
 3(3/2) + 7 = k
23/2 = k
 
 *kalo salah bagitahu    
                                
                           
2016-02-12T12:17:46+08:00
(2x - 1)(x + 4) = k (x - 1) + 3
2x² + 7x - 4 = kx - k + 3
2x² + 7x - kx + k - 4 - 3 = 0
2x² + (7 - k)x + k - 7 = 0

b² - 4ac = 0
(7 - k)² - 4(2)(k - 7) = 0
49 - 14k + k² - 8k + 56 = 0
k² - 22k + 105 = 0
(k - 15) (k - 7) = 0
k - 15 = 0
     k = 15
atau
k - 7 = 0
     k = 7